Making the Internet of Things Trainer Based on ESP-32 Microcontroller (Nusantara Science and Technology Proceedings, 2021)
The absence of teaching aids is still an obstacle in the learning process of Internet of Things (IoT)-based interfacing subjects where students have difficulty understanding the material obtained other than because of the lack of microcontroller practice experience that makes students less understanding how to operate a microcontroller and also because of a lack of basic knowledge about IoT. The design of the ESP-32 microcontroller-based IoT interface trainer is intended as a teaching aid to help understand the interfacing of microcontrollers using several protocols and can be used as an Internet of Things teaching aid to help students practice monitoring and controlling input-output on a microcontroller using a smartphone via the internet network. In designing this trainer, direct observations were made on learning activities for IoT and interfacing subjects as well as conducting questions and answers with several students. This trainer uses RFID, RTC and LCD modules as interfacing teaching aids that are connected to the ESP-32 microcontroller, and there are components in the form of LEDs and potentiometers to practice the concept of the Internet of Things. Pin headers for microcontroller interface pin expansion are also available on this trainer which can be connected to more modules and other components. The modules and components in this trainer design are connected to the ESP32 microcontroller in one integrated circuit board so as to provide practicality in using it.